Organocatalytic kinetic resolution of 1,5-dicarbonyl compounds through a retro-Michael reaction - James Guevara-Pulido; Fernando González-Pérez; José M. Andrés; Rafael Pedrosa (Beilstein Journal of Organic Chemistry)
The pharmaceutical chemical industry has long used kinetic resolution to obtain high-value compounds. Organocatalysis has recently been added to this strategy, allowing for the resolution of racemic mixtures with low catalyst loadings and mild reaction conditions. This research focuses on the kinetic resolution of 1,5-dicarbonyl compounds using a retro-Michael reaction, co-catalyzed at room temperature with 20 mol % of the Jørgensen–Hayashi catalyst and PNBA. The study highlights the importance of conducting the kinetic resolution at a concentration of approximately ten millimolar (mM) to prevent the Michael retro-Michael equilibrium from affecting the process.